2002
DOI: 10.1103/physrevlett.89.062301
|View full text |Cite
|
Sign up to set email alerts
|

H2(e,ep)nReaction at High Recoil Momenta

Abstract: The 2H(e,e(')p)n cross section was measured in Hall A of the Thomas Jefferson National Accelerator Facility near the top of the quasielastic peak (x(Bj)=0.964) at a four-momentum transfer squared, Q(2)=0.665 (GeV/c) (2) (omega=0.368 GeV, W=2.057 GeV), and for recoil momenta up to 550 MeV/c. The measured cross section deviates by 1-2sigma from a state-of-the-art calculation at low recoil momenta. At high recoil momenta the cross section is well described by the same calculation; however, in this region, final-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…2c) show a typical behavior of reduced 2 H(e, e p)n deuteron cross sections as a function of missing momentum, namely a 'flattening' of the cross section around p m > 0.3 GeV/c. This flattening has been observed in most previous measurements of the 2 H(e, e p)n cross section at lower Q 2 which have been taken either at [13] x B ∼ 1, where FSI dominates or at values x B < 1, where MEC and IC dominated [11]. From the measured angular distributions reported here and previously [28], we found that at this angle FSI contributions to the reaction are maximal.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…2c) show a typical behavior of reduced 2 H(e, e p)n deuteron cross sections as a function of missing momentum, namely a 'flattening' of the cross section around p m > 0.3 GeV/c. This flattening has been observed in most previous measurements of the 2 H(e, e p)n cross section at lower Q 2 which have been taken either at [13] x B ∼ 1, where FSI dominates or at values x B < 1, where MEC and IC dominated [11]. From the measured angular distributions reported here and previously [28], we found that at this angle FSI contributions to the reaction are maximal.…”
supporting
confidence: 86%
“…However, depending on the selected kinematics, these studies can be overwhelmed by final state interactions (FSI) where the outgoing proton interacts with the recoiling neutron, or by processes where the virtual photon couples to the exchanged meson (MEC) or where the nucleon is excited to an intermediate ∆ state (IC). The dominance of FSI, MEC and IC has seriously affected previous experiments at Q 2 < 1 (GeV/c) 2 [10][11][12][13][14] leading to the overall conclusion that these experiments do not provide good constraints on the high momentum components of the deuteron wave function.…”
mentioning
confidence: 99%
“…With the advent of JLab, the first (e, e p) experiments have been measured at large missing momentum on the quasi-elastic peak (x ≈ 1). The kinematics of these measurements corresponded to the large transverse component of missing momentum, resulting in a strong dominance of final-state interactions in the measured cross sections (84,85,86).…”
Section: Recent (Ee'p) Measurementsmentioning
confidence: 97%
“…The suggestion that the short-range behavior of the strong nuclear interaction could manifest itself through short-range nucleon-nucleon correlations and momentum distributions in a nucleus (Schroeder et al, 1979) refocused the need for a better understanding of, and therefore more intensive investigations into, these concepts. Hence, there are continued experimental (Egiyan et al, 2007;Jones et al, 2000;Ulmer et al, 2002) and theoretical (Alvioli et al, 2008;Frankfurt et al, 1993;Piasetzky et al, 2006) investigations of these concepts.…”
Section: Introductionmentioning
confidence: 99%